Decreased reticuloendothelial system clearance and increased blood half-life and immune cell labeling for nano- and micron-sized superparamagnetic iron-oxide particles upon pre-treatment with Intralipid - Liu, Li; Hitchens, T. Kevin; Ye, Qing; Wu, Yijen; Barbe, Brent; Prior, Devin E.; Li, Wendy F.; Yeh, Fang-Cheng; Foley, Lesley M.; Bain, Daniel J.; Ho, Chien (Biochimica et biophysica acta, 2013)
Superparamagnetic iron-oxide nanoparticles are useful as contrast agents for anatomical, functional and cellular MRI, drug delivery agents, and diagnostic biosensors. Nanoparticles are generally cleared by the reticuloendothelial system (RES), in particular taken up by Kupffer cells in the liver, limiting particle bioavailability and in-vivo applications. Strategies that decrease the RES clearance and prolong the circulation residence time of particles can improve the in-vivo targeting efficiency. Intralipid 20.0%, an FDA approved nutritional supplement, was intravenously administered in rats at the clinical dose (2g/kg) 1h before intravenous injection of ultra-small superparamagnetic iron-oxide (USPIO) or micron-sized paramagnetic iron-oxide (MPIO) particles. Blood half-life, monocyte labeling efficiency, and particle biodistribution were assessed by magnetic resonance relaxometry, flow cytometry, inductively-coupled plasma MS, and histology. Pre-treatment with Intralipid resulted in a 3.1-fold increase in USPIO blood half-life and a 2-fold increase in USPIO-labeled monocytes. A 2.5-fold increase in MPIO blood half-life and a 5-fold increase in MPIO-labeled monocytes were observed following Intralipid pre-treatment, with a 3.2-fold increase in mean iron content up to 2.60pg Fe/monocyte. With Intralipid, there was a 49.2% and 45.1% reduction in liver uptake vs. untreated controls at 48h for USPIO and MPIO, respectively. Intralipid pre-treatment significantly decreases initial RES uptake and increases in-vivo circulation and blood monocyte labeling efficiency for nano- and micron-sized superparamagnetic iron-oxide particles. Our findings can have broad applications for imaging and drug delivery applications, increasing the bioavailability of nano- and micron-sized particles for target sites other than the liver. [Display omitted] ► Intralipid targets the liver Kupffer cells and blunts nanoparticle clearance. ► Intralipid results in an ~50% decrease in liver uptake of USPIO and MPIO particles. ► Intralipid produces an ~3-fold increase in blood half-life of the particles. ► Intralipid causes a 2 to 5-fold increase in labeling efficiency of blood monocytes. ► Nanoparticles can target more diverse sites or organs, other than the liver.